Exertional Rhabdomyolysis after an Extreme Conditioning Competition: A Case Report - Ramires Alsamir Tibana; Nuno Manuel Frade de Sousa; Gabriel Veloso Cunha; Jonato Prestes; James W. Navalta; Fabricio Azevedo Voltarelli (MDPI AG, 2018)
This case report describes an instance of exercise-induced rhabdomyolysis caused by an extreme conditioning program (ECP) competition. A 35-year-old female presented with abdominal pain and soreness, which began one day after she completed two days of ECPcompetition composed of five workouts. Three days after competition, creatine kinase (CK) was 77,590 U/L accompanied by myalgia and abnormal liver function tests, while renal function was normal and this resulted in a diagnosis of rhabdomyolysis. A follow-up examination revealed that her serum level of CK was still elevated to 3034 U/L on day 10 and 1257 U/L on day 25 following the ECP competition. The subject reported myalgia even up to 25 days after the ECP competition. Exertional rhabdomyolysis can be observed in ECP athletes following competition and highlights a dangerous condition, which may be increasing in recent years due to the massive expansion of ECP popularity and a growing number of competitions. Future research should investigate the causes of rhabdomyolysis that occur as a result of ECP, especially training methods and/or tasks developed specifically for these competitions.